Germination success and drought response in Erica coccinea - Leonard, Jenny (Department of Biological Sciences, 2015)
Resprouters and seeders are two common phenotypes found in fire-prone ecosystems. Although the distribution of the two forms is usually attributed to fire frequency, it has been proposed that the distribution of resprouter and seeder Erica in the Cape Floristic Region (CFR) of South Africa is determined more by water availability. Erica seeders are predicted to withstand the mild droughts of the southwest CFR better than Erica resprouters, which would account for the abundance of seeders in this region. This thesis tested the assumptions that 1) seeders germinate more quickly and successfully than resprouters and 2) seeders survive mild drought better than resprouters. A germination experiment (Chapter 2) and a drought experiment (Chapter 3) were conducted using Erica coccinea, a common Erica species in the CFR, which contains both a resprouter and a seeder form. Germination success was also tested for a third form of E. coccinea found only in fire refugia. I predicted that this form would not require smoke as a cue for germination. Results indicated that (1) resprouters germinated faster than seeders in the presence of smoke, (2) seeders had better germination success than resprouters in the absence of smoke, (3) the "pyrofuge" form did not require smoke to germinate and (4) seeders had lower survival than resprouters during drought. Overall, these results refuted the proposition that E. coccinea seeders have improved germination and drought tolerance. However, variation between populations within the seeder form indicated that more populations should be tested to verify that these results represent the species as a whole. Due to the lack of variation between populations of the "pyrofuges", it is clear that this form has adapted to its' fire-free environment by allowing for germination in the absence of fire.